2017
DOI: 10.3892/ol.2017.7535
|View full text |Cite
|
Sign up to set email alerts
|

LATS2 promoter hypermethylation and its effect on gene expression in human breast cancer

Abstract: Abstract. Tumor-specific promoter hypermethylation of large tumor suppressor, homolog 2 (LATS2), a tumor suppressor gene, has been investigated using methylation-specific polymerase chain reaction (MSP) assays in different types of human cancer producing conflicting results. The aim of the present study was to evaluate the methylation status of the LATS2 promoter region using bisulfite sequencing with a next generation sequencer for breast cancer. In the 11 patients enrolled in the present study, the LATS2 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This study found that LATS2 was down-regulated in gastric cancer. The finding was consistent with the previous study [44].…”
Section: Discussionsupporting
confidence: 94%
“…This study found that LATS2 was down-regulated in gastric cancer. The finding was consistent with the previous study [44].…”
Section: Discussionsupporting
confidence: 94%
“…Consistently, our data showed that PAX6 can result in LATS2 hypermethylation. A recent study reported that LATS2 hypermethylation is not involved in silencing the mRNA expression of LATS2 mRNA 70 . However, the absence of LATS2 protein strongly correlates with promoter hypermethylation, where 91 of a total of 107 hypermethylated cases displayed the absence of protein 71 .…”
Section: Discussionmentioning
confidence: 97%
“…A recent study reported that LATS2 hypermethylation is not involved in silencing the mRNA expression of LATS2 mRNA. 70 However, the absence of LATS2 protein strongly correlates with promoter hypermethylation, where 91 of a total of 107 hypermethylated cases displayed the absence of protein. 71 Therefore, it is unclear whether LATS2 hypermethylation contributes to decreased LATS2 expression, and whether PAX6 promoting LATS2 hypermethylation is the key mechanism by which PAX6 regulates LATS2 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that decreased MST1 transcript expression is correlated with methylation of its promoter region 27 . Additionally, methylation alterations frequently inactivate LATS2, making the Hippo signaling pathway unable to control caner development 33 .…”
Section: Discussionmentioning
confidence: 99%